Confinement during Covid-19 outbreak modifies athletes' self-based goals. (November 2020) - Mascret, Nicolas
Abstract: Because achievement goals are context-specific, the study first investigated the evolution of two achievement goals of 697 regular athletes, namely self-approach goals (improving oneself) and self-avoidance goals (avoiding regression), before and during the confinement situation and the physical exercise restrictions due to the Covid-19 outbreak. Secondly, we sought to examine the potential predicting role of self-approach and self-avoidance goals on athletes' intention to exercise during confinement, while self-avoidance goals were usually not related to this outcome in a more traditional context. Using a retrospective correlational design, the results of repeated measures ANOVA highlighted that self-approach goals scores decreased while self-avoidance goals scores increased and became the athletes' goals with the highest score during confinement. The results of hierarchical regression analyses showed that self-approach and self-avoidance goals were both found as positive predictors of intention to exercise during confinement. This study reinforces the assumptions that (a) a specific achievement setting encourages the adoption of different achievement goals (which was identified here with regular athletes in an unusual context of confinement), (b) self-avoidance goals are not always maladaptive, and (c) shifting among multiple goals according to the requirements of the situation may be beneficial. Highlights: Different achievement goals may be better suited for different types of situations. Athletes' self-based goals changes during the Covid-19 outbreak. Athletes focus on avoiding physical regression (self-avoidance goals). Self-avoidance goals are not always maladaptive and predict intention to exercise. Shifting among multiple goals according to the situation may be beneficial.